The Influence of pH on Structural, Morphological, and Optical Properties of Al2O3 Nanoparticles Synthesized by Syzygium aromaticum Leaf Extract - Anggara Budi Susial; Natasya Frysillia Wardani; Rahmat Setiawan Mohar; Nurfina Yudasari; Artoto Arkundato; Suhendar, Haris; Hadi Nasbey; Imam Basori; Tan Swee Tiam; Iwan Sugihartono (Jurnal Sains Materi Indonesia, 2026)
Aluminum oxide (Al2O3) nanoparticles have been synthesized through a biosynthesis approach, employing Syzygium aromaticum leaf extracts prepared under varying acidic conditions as bioreductants in the reaction with aluminum nitrate nanohydrate. The Al2O3 nanoparticles were annealed at 450 °C for one hour to facilitate the formation. Then, the samples were characterized for their crystal structure, morphology, and optical properties using X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), and UV-visible (UV-Vis) spectrophotometry, respectively. XRD analysis confirmed that the Al2O3 nanoparticles possess an orthorhombic crystal structure, corresponding to Inorganic Crystal Structure Database (ICSD) entry #98-009-4485. The average crystallite sizes were measured to be 37.36 nm, 15.47 nm, and 12.52 nm for nanoparticles synthesized at pH-9, pH-10, and pH-11, respectively. Morphologically, the pH condition affects the morphology of Al2O3 nanoparticles. The reflectance spectrum peak of Al2O3 nanoparticles in the wavelength range of 328–336 nm is observed with the band gap energy of 2.92-3.01 eV. According to these results, it is believed that the Al2O3 nanoparticles have potential applications as photocatalysts.